2023
DOI: 10.1098/rspb.2023.0204
|View full text |Cite
|
Sign up to set email alerts
|

Singing humpback whales respond to wind noise, but not to vessel noise

Abstract: Animal communication systems evolved in the presence of noise generated by natural sources. Many species can increase the source levels of their sounds to maintain effective communication in elevated noise conditions, i.e. they have a Lombard response. Human activities generate additional noise in the environment creating further challenges for these animals. Male humpback whales are known to adjust the source levels of their songs in response to wind noise, which although variable is always present in the oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…In addition, the noise considered was from a fishing boat rather than commercial shipping and was therefore lower in amplitude. Thus, the findings presented here are intermediate between those reported by Tsujii et al [7] and Girola et al [8] in the sense that this whale continued to sing in the presence of elevated shipping noise but did modify the song structure substantially. Whether a change in the source level of units also occurred (i.e., a Lombard effect) is the focus of an ongoing analysis.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In addition, the noise considered was from a fishing boat rather than commercial shipping and was therefore lower in amplitude. Thus, the findings presented here are intermediate between those reported by Tsujii et al [7] and Girola et al [8] in the sense that this whale continued to sing in the presence of elevated shipping noise but did modify the song structure substantially. Whether a change in the source level of units also occurred (i.e., a Lombard effect) is the focus of an ongoing analysis.…”
Section: Discussioncontrasting
confidence: 95%
“…Their findings revealed that whales reduced or stopped singing when a ship passed within 500-1200 m, or in some cases after it had passed. In contrast, Girola et al [8] reported that, although humpback whales changed the source level of singing in response to wind noise, they did not make changes in response to vessel noise. However, that study focused on the lack of a Lombard effect in relation to vessel noise and did not examine changes in song structure.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, in the vicinity of torrent streams where fast-flowing water creates low-frequency noise, many anuran frog species increase their calling frequencies to prevent their calls from being masked by ambient noise (Goutte et al, 2018). Likewise, humpback whales (Megaptera novaeangliae) increase the levels of their social vocalisations in response to elevated wind-dependent ambient noise (Dunlop et al, 2014;Girola et al, 2023aGirola et al, , 2023b.…”
mentioning
confidence: 99%